2004
DOI: 10.1093/jxb/erh051
|View full text |Cite
|
Sign up to set email alerts
|

Gating of water channels (aquaporins) in cortical cells of young corn roots by mechanical stimuli (pressure pulses): effects of ABA and of HgCl2

Abstract: Hydraulic properties (half-time of water exchange, T1/2, and hydraulic conductivity, Lp; T1/2 approximately 1/Lp) of individual cells in the cortex of young corn roots were measured using a cell pressure probe for up to 6 h to avoid variations between cells. When pulses of turgor pressure of different size were imposed, T1/2 (Lp) responded differently depending on the size. Pulses of smaller than 0.1 MPa, which induced a small proportional water flow, caused no changes in T1/2 (Lp). Medium-sized pulses of betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
177
4
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(195 citation statements)
references
References 42 publications
13
177
4
1
Order By: Relevance
“…Data are means 6 SD of n = 6 microcapillaries tested. (Wan et al, 2004). For the latter hydraulic disturbance, we have similarly noted increased T 1/2 in T. virginiana epidermal cells when applying P steps of greater than 0.15 MPa (data not shown).…”
Section: Cell Water Relations Parameters Of T Virginiana Leaf Epidersupporting
confidence: 52%
See 1 more Smart Citation
“…Data are means 6 SD of n = 6 microcapillaries tested. (Wan et al, 2004). For the latter hydraulic disturbance, we have similarly noted increased T 1/2 in T. virginiana epidermal cells when applying P steps of greater than 0.15 MPa (data not shown).…”
Section: Cell Water Relations Parameters Of T Virginiana Leaf Epidersupporting
confidence: 52%
“…Consistent with other studies in higher plant cells, Moore and Cosgrove (1991) Cosgrove and Steudle (1981) reported that a substantial (6-fold) and rapid (within 20 s) reduction in L p could occur in the same cell, and in hindsight, this presumably reflected the influence of aquaporins. Cosgrove and Steudle (1981) did not consider the lower L p as indicative of the L p in situ, and Wan et al (2004) reported that a reduction in L p was associated with perturbations to P cell on the order of 0.1 MPa. Hence, if measured membrane L p itself can exhibit substantial changes over relatively short periods of time in the same cell, then further study of systematic differences between L p OUT and L p IN will require a robust hydrostatic methodology (PC or PR) that can reversibly and reproducibly apply small perturbations in pressure (P) to individual cells over short periods of time.…”
mentioning
confidence: 99%
“…5). Wan et al (2004) proposed a gating mechanism for AQPs which involves the water flow rate through AQPs. This gating mechanism will affect cellular water status and, through this, could provide the link between xylem tension, cellular water flow rate and nuclear AQP transcription response.…”
Section: The Signal Affecting Root Aqp Expression and Lpmentioning
confidence: 99%
“…There is no direct evidence for mechanosensitivity of aquaporin proteins, although some studies illustrate the potential for MIPS to be involved in volume or turgor homeostasis in plants [3,73,74], and a different mechanism of mechanical inhibition was recently reported in young maize roots [75]. The dependence of mercury-induced closure of water channels on tissue turgor indicates that changes in turgor can induce changes in the conformation of the plasma membrane, or even in the aquaporins themselves [76].…”
Section: Effects Of Turgor and Osmotic Pressure On Aquaporin Activitymentioning
confidence: 99%
“…The responsiveness of each aquaporin to ABA were different, implying that the regulation of aquaporin expression involves both ABA-dependent and ABA-independent signaling pathways. Both energy-input and tension-gating mechanisms might be used by the plant to sense changes in turgor pressure and surrounding water availability, and to adapt the membrane water permeability in an ABAdependent manner [75]. In many species including sunflower, barley, sorghum and maize [96][97][98], exogenous ABA enhanced root L p .…”
Section: Relationships Between Plant Aquaporins and Hormonesmentioning
confidence: 99%